Polygonisation of disjoint implicit surfaces by the adaptive edge spinning algorithm of implicit objects. (10th July 2007) - Cermak, Martin; Skala, Vaclav
This paper presents an adaptive method for polygonisation of implicit surfaces. The method is based on the shape of triangles and the accuracy of resulting approximation. The main advantages of the triangulation presented are simplicity and the stable features that can be used for the next expansion. The presented algorithm is based on the surface tracking scheme, and it is compared with other algorithms that are based on the similar principle, such as the Marching cubes and the Marching triangles algorithms. Moreover, the technique for detection of more disjoint implicit surfaces in a defined area is also presented. The algorithm is not limited to a given polygonisation method, but then its use is possible for all other surface approaches that need a starting point at the beginning.